Religious Awareness Analysis for Disability Groups - Ajeng Linda Liswandari; Anita Puji Astutik (Dialogia, 2021)
This article wants to explain the problems of people with disabilities in forming religious awareness. For this reason, it is necessary to know more about the perspective of being aware of religion, the assumption of being aware of religion, efforts to increase religious awareness for people with disabilities. This research method uses qualitative research with a phenomenological or interpretive paradigm. This qualitative research was conducted through a descriptive approach with field studies. The subject of this research was carried out on the management of the Disable Motorcycle Indonesia community in East Java, especially the Sidoarjo area, which consisted of 7 people. Examining religious awareness, the reality of the manifestation starting from worship and religious deepening seems to have not been carried out comprehensively and massively. The will and enthusiasm of people with physical disabilities is not enough to raise religious awareness. Full support is needed through public services, correlation between relationships that form emotions and opportunities for people with disabilities. Thus, religious rights and obligations are not in the right proportion. Efforts can be made in the form of awareness campaigns that disability is close to the congregation. And to fulfill equal religious needs, the government must fulfill religious rights according to the 1945 Constitution, Law on Persons with Disabilities, Ratification of the Convention on the Rights of People with Disabilities.